Bladder cancer - Fabian, Alexander; Domschikowski, Justus; Dunst, Jürgen; Ott, Oliver (Springer International Publishing, 2024)
This chapter offers insights into radiotherapy of patients with bladder cancer based on latest evidence and consensus guidelines. Emphasis is placed on radical radiotherapy in the context of organ-preserving trimodal therapy of muscle-invasive bladder cancer. Patient selection as well as dose and fractionation of radiotherapy are outlined. Guidance on target volume definition is presented in detail per gross tumor volume, clinical target volume, and planning target volume. This includes a discussion of elective nodal irradiation and whole vs. partial bladder radiotherapy. Adequate concepts of radiotherapy are also proposed for cases treated in palliative intent. Furthermore, special treatment techniques are introduced including image-guided radiotherapy and adaptive radiotherapy. Didactic figures accompany the chapter and aid to convey the role and principles of radiotherapy for bladder cancer.
CRIS-Team Scopus Importer:2024-12-06